EFFECT OF JAPAN WATER THERAPY INFUSED WITH CINNAMON ON BODY WEIGHT, WAIST/HIP RATIO, AND BODY MASS INDEX OF OVERWEIGHT AND OBESE SUBJECTS - SHIVANI BHATIA,; SHUBHRA SARASWAT, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to discover the effect of Japan water therapy with cinnamon on body composition in overweight and obese subjects. Methods: The study was conducted with 36 subjects divided into three groups, namely, Group A – water therapy with cinnamon (n=12), Group B – water therapy (n=12), and Group C – warm water (n=12), where Groups A and B were test groups and Group C was a control group. This study was carried out for 8 weeks. Body weight, waist/hip ratio (WHR), and body mass index (BMI) were measured every 15th day. Data were statistically analyzed by mean, standard deviation, and paired t-test using Getcalc.com Results: Out of all the groups, Group A showed desirable reduction in weight, WHR, and BMI, but statistically it was non-significant on WHR. Similarly, Group B had non-significant result with content to WHR but showed a moderate reduction in all categories. However, Group C as a control group both had either constant or minimal reduction in WHR and BMI being statistically non-significant. Conclusion: The findings of the study concluded that consumption of Japan water therapy with cinnamon helps in reduction of weight, WHR, and BMI within 8 weeks. Plain water therapy only had a moderate effect on reducing body composition in the same duration of time.